2021
DOI: 10.1002/celc.202100724
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Liquid State Electrochemistry Coupled with NMR Spectroscopy

Abstract: Analytical methods of electrochemistry (EC) are relatively inexpensive, and widely used in science, industry, and medicine. Although EC is distinguished by its high sensitivity, it does not provide direct and detailed data about the bond connectivity or dynamics of the molecular system. Conversely, Magnetic Resonance (MR) gives comprehensive insights into the structure and dynamics of molecules but suffers from low sensitivity. The strengths and shortcomings of EC and NMR are thus complementary. The combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…Table shows a summary of the main characteristics of some setups used for in situ coupling between NMR and electrochemistry. More information on current developments in the area of coupling between electrochemistry and liquid NMR can be found in the recent review published in 2021 by Pietrzak et al…”
Section: Resultsmentioning
confidence: 99%
“…Table shows a summary of the main characteristics of some setups used for in situ coupling between NMR and electrochemistry. More information on current developments in the area of coupling between electrochemistry and liquid NMR can be found in the recent review published in 2021 by Pietrzak et al…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the measurement of pH is demonstrated in an electrochemical cell and during electrolysis by in operando nuclear magnetic resonance (NMR), which has proven capable of investigating the (aq)/ / equilibrium in such an environment 25 . The method takes advantage of the high spectral resolution and sensitivity afforded by this cell design even in the presence of electrically conductive material 26 . In contrast to methods that only consider either the (aq)/ 22 or the / equilibrium 24 , the presented method provides data for a wider pH range by considering both equilibria, including an overlap region in-between.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical cells for in operando NMR measurements were developed and improved over the past 45 years [26][27][28][29][30] , but high spectral resolution and sensitivity even in the presence of conductive material in the sensitive volume of the NMR setup has been demonstrated only recently. To calculate the pH from in operando 13 C NMR data, we utilize the buffer capability of HCO -3 /CO 2 -3 .…”
Section: Introductionmentioning
confidence: 99%